Organometric parameters of the spleen in persons of different genders, ages and physiques: current data and research prospects - A. S. Dadashev; I. S. Miltykh; D. A. Sukmanova; V. A. Mishin; O. K. Zenin; E. S. Kafarov (Сибирский научный медицинский журнал, 2025)
Splenectomy (removal of the spleen) and splenorrhaphy (spleen suturing) remain the leading treatments for patients with severe organ injuries. These surgeries require a thorough understanding of the anatomy of the spleen. The aim of the study was to present modern data on organometric parameters (length, width, thickness and volume) of the spleen in individuals of different sex, age and physique. Within the study we conducted a systematic search and analyses of sources in bibliographic databases Scopus, Web of Science, PubMed and Russian Science Citation Index (RSCI). The statistical software R (version 4.1) was used. As a result of meta-analysis, it was found that the weighted mean values of length, width and volume of the spleen are: 10.46 cm, 6.43 cm, and 205.43 cm3, respectively. The researchers observed a tendency for the its length to increase as body length increases. It is also found that spleen volume is significantly greater in males (254.20 cm3) than in females (185.11 cm3). Understanding of the actual organometric characteristics of the spleen will contribute to the improvement of methods of early diagnosis of diseases, objective assessment of treatment and prevention of its pathology and, as a consequence, to the improvement of the quality of medical care.